PENGEMBANGAN KOMPETENSI APARATUR DI SEKRETARIAT DAERAH KABUPATEN MAHAKAM ULU - Roosilawati Arham Jonathan (Jurnal Paradigma (JP), 2017)
The  purpose  of  this study  was to  describe and  analyze  the Competence  Development  Apparatus. The results of the research indicate that developing competence of apparatus in Mahakam Ulu District Secretariat, has brought changes increase the Competance of the apparatus. That indicates by some sub focus  of  the research  that  show  there  are  increment  competence, review  by formal  legality aspect it  appear that development of apparatus competence can increase amount of educated civil  servant such as bachelor’s degree and Master’s Degree.  Less  optimum  of  the  developing  competence  program  cause  by  the  limited  estimate  allocated  for  developing  of  human  resource  specially  for  formal  education  and  various  of  training.  Various  of  awareness  the  employee  in  perceive  the  important  of  developing   work   ability   through   formal   education   and   various   of   traning  for  the   civil   servant   that   can   support   the    work   continuity   so   the  work   result   do not fulfill the qualification that expect .